2019
DOI: 10.1002/ange.201814552
|View full text |Cite
|
Sign up to set email alerts
|

Assemblies of Peptides in a Complex Environment and their Applications

Abstract: Using peptide assemblies with emergent properties to achieve elaborate functions has attracted increasing attention in recent years. Besides tailoring the self‐assembly of peptides in vitro, peptide research is advancing into a new and exciting frontier: the rational design of peptide assemblies (or their derivatives) for biological functions in a complex environment. This Minireview highlights recent developments in peptide assemblies and their applications in biological systems. After introducing the unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…[4][5][6] What is more, enzyme-regulated peptide-based nanostructures have been designed to achieve enhanced bioactivity for the treatment of various diseases in living systems. [7][8][9][10][11][12] However, the self-assembled peptide materials that are formed by physical-cross-linking (i.e., non-covalent interactions) usually demonstrate weak mechanical properties and uncontrollable drug release profiles, which make them difficult to apply in the field of biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] What is more, enzyme-regulated peptide-based nanostructures have been designed to achieve enhanced bioactivity for the treatment of various diseases in living systems. [7][8][9][10][11][12] However, the self-assembled peptide materials that are formed by physical-cross-linking (i.e., non-covalent interactions) usually demonstrate weak mechanical properties and uncontrollable drug release profiles, which make them difficult to apply in the field of biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, artificially designed peptides can generate various architectures [including fibers, tapes, tubes, sheets, and spheres ( Acar et al, 2017 )] in vitro , demonstrating the considerable potential for carrier-mediated drug delivery, tissue engineering, antimicrobial agents, imaging tools, energy storage, biomineralization, and membrane protein stabilization ( Mandal et al, 2014 ). On the other hand, peptides and relative derivatives have been developed as effective navigation systems to selectively target organelles, e.g., endoplasmic reticulum ( Field et al, 2015 ; Wang et al, 2019 ), mitochondria ( Szeto et al, 2011 ; Jean et al, 2016 ), or nucleus ( Beyer et al, 2015 ; Yumerefendi et al, 2015 ). Since the exact localization of proteins is required to fulfill their biological functions ( Itzhak et al, 2016 ), transportation of functional proteins or peptides to orientated intracellular localization is a prerequisite to intensify their functions in application areas ( Niopek et al, 2014 ; Guntas et al, 2015 ) or to study their mechanism in basic research fields ( Drake et al, 2010 ; Slootweg et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, enzyme-instructed self-assembly (EISA) has emerged as a novel strategy to enhance selectivity of anticancer drugs through exploiting various enzymes that are overexpressed in cancer cells. Under the catalysis of these enzymes, hydrogel precursors are transformed to hydrogelators, which self-assemble in an aqueous solution to give nanofibrillar structures in a cell milieu. For example, Wu et al reported that self-assembly of a peptide derivative, which was triggered by intracellular alkaline phosphatases (ALP), displayed excellent selectivity toward cervical cancer cells . Therefore, it appears to be a viable option to integrate NSAIDs with an EISA process to further enhance the selectivity of NSAIDs toward cancer cells.…”
Section: Introductionmentioning
confidence: 99%